RECTAL ADENOCARCINOMA: CLINICAL EVALUATION AND TREATMENT THROUGH ROBOTIC SURGERY - Amaral, Felipe Leão Martins; Ramos, Júlia Cristina de Sousa; Costa, Mariany Rodrigues; Rodrigues, Maria Clara Silva; Ribeiro, Roberta Cristina Lourençoni; Rezende, Eduardo Henrique Mendes; Borges, Luiz Augusto Germano; Filho, Murilo Dell Eugenio Costa; Maciel, Ana Luisa Silva; Silva, Luana Dutra Pinheiro da; Bertin, Lethícia Mariah Marchi; Garcia, Ariane Simião (Brazilian Journal of Implantology and Health Sciences, 2024)
Rectal adenocarcinoma is a malignant neoplasm that develops in the glandular cells of the rectum. Its clinical evaluation and treatment have been objects of considerable interest, especially with the advancement of robotic surgery. The introduction of the robot in colorectal surgery has provided significant advantages, such as better visualization, precision and control of movements, resulting in potential benefits for patients. However, the literature on the effectiveness and outcomes of robotic surgery in the treatment of rectal adenocarcinoma is vast and varied. Objective: to examine and synthesize the available evidence on the clinical assessment and treatment of rectal adenocarcinoma using robotic surgery, focusing on the last 10 years. Methodology: The methodology followed the PRISMA checklist guidelines. We used the PubMed, Scielo and Web of Science databases to identify relevant articles published in the last 10 years. The descriptors used were "rectal adenocarcinoma", "robotic surgery", "clinical evaluation", "treatment" and "results". The inclusion criteria were studies that evaluated robotic surgery in the treatment of rectal adenocarcinoma, published in English or Portuguese. The exclusion criteria were studies unrelated to the topic, studies without access to the full text and studies with duplicate data. Results: The results revealed an increasing trend in the use of robotic surgery for the treatment of rectal adenocarcinoma. Key topics covered included oncological outcomes, postoperative complications, post-treatment quality of life, and comparisons with other surgical approaches. Conclusion: The review highlights the growing evidence supporting the efficacy and safety of robotic surgery in the treatment of rectal adenocarcinoma. However, additional studies are needed to further understand its clinical utility and its long-term impact on patient outcomes.